ANALISIS EFEKTIVITAS PAJAK DAERAH DI PROVINSI PAPUA - Jemy Ricardo Parera (Jurnal Ekonomi dan Bisnis, 2017)
This study aims to determine how much the effectiveness of local taxes in the province of Papua This research was carried out in all areas of Papua. The data used in this study is secondary data obtained from Bank Indonesia and the Central Bureau of Statistics through internet facilities. Estimation, analysis in the study was carried out using annual data from 2012-2016. The data were analyzed using the effectiveness method. The results showed that knowing the level of effectiveness of Papua Province local tax revenues, to determine the factors that affect the level of Papua Province local tax revenues. The result of this study is that the growth of Papua Province regional tax revenues during the last five years has fluctuated, both targets and realizations. The highest growth occurred in 2012 at 48.53% and in 2016 it decreased to -6.32%. In the last five years, from 2012-2016 Papua Province regional tax revenues experienced a very good level of effectiveness or in other words Papua Province regional taxes were 90% effective. Where in 2014 was the highest achievement of 121.10% and in 2015 was the lowest achievement of 83.64%.